2015
DOI: 10.1093/mnras/stv1614
|View full text |Cite
|
Sign up to set email alerts
|

The MAGellanic Inter-Cloud (MAGIC) project – II. Slicing up the Bridge

Abstract: The origin of the gas in between the Magellanic Clouds (MCs), known as the Magellanic Bridge, has always been the subject of controversy. To shed light into this, we present the results from the MAGellanic Inter-Cloud II (MAGIC II) project aimed at probing the stellar populations in 10 large fields located perpendicular to the main ridge-line of H I in the Inter-Cloud region. We secured these observations of the stellar populations in between the MCs using the WFI (Wide Field Imager) camera on the 2.2 m telesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 82 publications
1
44
0
Order By: Relevance
“…By examining the Bridge between the LMC and SMC, we gain insight into the structure of the system and their history of interactions. Studies have shown that the young and intermediate age stars in the MB have a clumpy, non-uniform distribution (Noël et al 2013(Noël et al , 2015Skowron et al 2014). The asymmetric locations of these stellar populations suggest that either they formed in situ or were stripped from the LMC or the SMC during an interaction.…”
Section: Extinction Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…By examining the Bridge between the LMC and SMC, we gain insight into the structure of the system and their history of interactions. Studies have shown that the young and intermediate age stars in the MB have a clumpy, non-uniform distribution (Noël et al 2013(Noël et al , 2015Skowron et al 2014). The asymmetric locations of these stellar populations suggest that either they formed in situ or were stripped from the LMC or the SMC during an interaction.…”
Section: Extinction Analysismentioning
confidence: 99%
“…Such an interaction is thought to have triggered star formation in the MB, as pointed out by Grondin, Demers & Kunkel (1992); Mizuno et al (2006); Skowron et al (2014); Chen et al (2014). However, based on their ages, the young stars could have either formed in situ in the MB, or formed in the SMC and been tidally stripped from it in the past ∼ 200 Myr (Noël et al 2015). Skowron et al (2014) find that although the young stellar populations in the MB tend to be concentrated near the SMC, there is evidence for a continuity of a young population throughout the Bridge region, consistent with the HI densities.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies by Demers & Battinelli (1998) and Harris (2007) did not find the presence of intermediate-age/old stellar populations in fields centred on the H i ridge line of the MB. However, recent studies (Bagheri, Cioni & Napiwotzki 2013;Noël et al 2013Noël et al , 2015Skowron et al 2014) found evidence of the presence of intermediate-age/old stellar populations in the central and western regions of the MB.…”
Section: Introductionmentioning
confidence: 99%
“…These authors suggested that it is the tidally stripped stellar counterpart of the H i in the MB. From their analysis of a few fields in the MB, Noël et al (2013Noël et al ( , 2015 found from the synthetic colour-magnitude diagram (CMD) fitting technique that the intermediate-age population in the MB has similar properties to stars in the inner ∼ 2.5 kpc region of the SMC and suggested that they were tidally stripped from the inner SMC region. Meanwhile, Skowron et al (2014), who studied a more complete region of the MB, explained the presence of intermediate-age stars as the overlapping haloes of the MCs.…”
Section: Introductionmentioning
confidence: 99%